A model for SME satisfaction towards online food delivery service system: a business to business perspective / Mohd Anuar Sulaiman - Sulaiman, Mohd Anuar (2024)
A number of studies have been conducted from the perspective of customers towards Online Food Delivery (OFD) service systems and parcel-hailing (P-hailing) which refers to the delivery of food, drinks, and parcels using motorcycles, but very few studies have been done from the perspective of the Small Medium Enterprise (SMEs) of food business operators towards OFD service. Although OFD service bring benefits and motivate SMEs to outsource food delivery services, report shows the existence of dissatisfaction from the three major stakeholders of OFD service, which are consumers, SMEs, and riders. Thus, it is important to conduct a study and build a model on SMEs satisfaction towards the OFD service in Malaysia. This research aims to study the factors that contribute to SMEs satisfaction and develop a satisfaction model of SMEs towards OFD service in Malaysia. 450 questionnaires have been distributed to the owners of small and medium-sized enterprises (SMEs) in the food and beverage (F&B) sectors throughout Malaysia. Out of the 450 questionnaires distributed, 424 respondents answered the questionnaire, and 411 respondents completed the questionnaire in its entirety, which was used for data analysis. The SmartPLS package was used to test direct effects models and effects models of intermediate variables using the whole and sample samples. The overall sample refers to the total sample of the study (411 SMEs owners). The research suggested that fourteen main factors contribute to vendor satisfaction, which are service quality tangibility, service quality reliability, service quality responsiveness, service quality assurance, service quality empathy, e-quality efficiency, e-quality fulfilment, e-quality privacy, e-quality contact, increase revenue, reduce burden, cost saving, price and customer satisfaction. The study results also suggested that the five most significant factors are service quality tangibility, increased revenue, reduced burden, price and customer satisfaction. It is hoped that the study can contribute to the improvement of services provided by food delivery operators in Malaysia.